(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Based on the basic law of flat interlocking, the paper considers a possibility of increasing the gear ratio of low module involute cylindrical planetary gears by using asymmetric tooth profile for the purposes of measuring devices. An example of the synthesis of such reduction gearing by optimal choice of asymmetry between the profiles and Possibility of generation III is presented. Also presented is a planar matching of the unconditional existence areas in the field of independent coefficients of instrument displacement by the straight optimization method and pre-set qualitative indicators of the gearing.